Synthesis of D–D–A-type small organic molecules with an enlarged linker system towards organic solar cells and the effect of co-adsorbents on cell performance. (23rd November 2015) - Kumavat, Priyanka P.; Baviskar, Prashant K.; Sankapal, Babasaheb R.; Dalal, Dipak S.
Abstract : The synthesis of two D–D–A type novel small molecules and their applications in organic solar cells have been studied. Abstract : The synthesis of two D–D–A type novel small molecules bearing N, N -dimethyl/ethyl aniline as a donor and a methine unit connected with cyano and carboxyl groups as an acceptor linked with conjugated π-linkers has been performed. The obtained compounds were characterized by using FT-IR, 1 H-NMR, 13 C-NMR, LC-HR-MS, TGA, FE-SEM and UV-Vis spectroscopic techniques. These designed small organic molecules have been utilized for the fabrication of novel organic solar cells on high surface area titanium dioxide films consisting of interconnected nanoparticles with the device configuration FTO/TiO2 /organic compound/electrolyte/platinum. The effect of cholic acid and dodecylamine as co-adsorbents with an organic compound has been studied towards the device performances and the results are incorporated herein.